Seismic Retrofitting of Non-Seismically Designed RC Beam-Column Joints using Buckling-Restrained Haunches: Design and Analysis. Issue 7 (9th August 2018) - Wang, Bin; Zhu, Songye; Xu, You-Lin; Jiang, Huanjun
ABSTRACT: Many existing reinforced concrete (RC) structures around the world have been designed to sustain gravity and wind loads only. Past earthquake reconnaissance showed that strong earthquakes can lead to substantial damage to non-seismically designed RC buildings, particularly to their beam-column joints. This paper presents a novel retrofit method using buckling-restrained haunches (BRHs) to improve the seismic performance of such joints. A numerical model for RC joints is introduced and validated. Subsequently, a new seismic retrofit strategy using BRHs is proposed, aimed at relocating plastic hinges and increasing energy dissipation. The results indicate the retrofit method can effectively meet the performance objectives.